Political Instability and Growth : The Central African Republic - Ghura, Dhaneshwar (IMF Working Papers; Working Paper ;, 2004)
This paper provides empirical evidence that the propensity for political instability in the Central African Republic (C.A.R.) has been increased by low tax revenues and deteriorations in the terms of trade. The direct effect of political instability on economic growth is not statistically significant, once account is taken of domestic investment, and economic growth in neighboring countries. The policy implications are: (i) mobilization of domestic revenues to pay public employees' salaries and provide basic social services would lower the probability of coups; (ii) economic diversification would reduce the propensity for adverse terms of trade shocks to fuel coups; and (iii) neighboring countries' efforts to resolve conflicts and achieve sustained growth would be beneficial for the C.A.R.'s economic performance.